2013
DOI: 10.1016/j.bbmt.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution Kinetics as an Early Predictor for Mortality using Various Hematopoietic Stem Cell Sources in Children

Abstract: The severity of complications of allogeneic hematopoietic stem cell transplantation (HSCT) is governed mainly by the status of immune reconstitution. In this study, we investigated differences in immune reconstitution with different cell sources and the association between the kinetics of immune reconstitution and mortality. Immunophenotyping was performed every 2 weeks in children who had undergone HSCT between 2004 and 2008 at University Medical Center Utrecht. Lymphocyte reconstitution in the first 90 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
112
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 58 publications
6
112
1
4
Order By: Relevance
“…25 Our data focusing on adult patients showed that T-cell recovery was at least not inferior and appeared to be similar in CB and BM recipients (data not shown). On the other hand, compared with BM and PB, CB was superior for B-cell recovery.…”
Section: Discussionmentioning
confidence: 91%
“…25 Our data focusing on adult patients showed that T-cell recovery was at least not inferior and appeared to be similar in CB and BM recipients (data not shown). On the other hand, compared with BM and PB, CB was superior for B-cell recovery.…”
Section: Discussionmentioning
confidence: 91%
“…For future research, analysis of the relation between cellular reconstitution (for example, CD4 þ count) and IFI might be a valuable contribution to this study. 21 Additional areas of interest are strategies to improve immune-reconstitution and adjuvant immunotherapies to prevent or treat fungal infections. Although the speed of neutrophil engraftment was not significantly associated to the occurrence of IFI, very early engraftment (o14 days) may impact outcomes, as may the use of combined CB/haploidentical transplants.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Hence, it is important to understand which factors affect IR and what mechanisms are involved. To our knowledge, we are the first to show IR in context of in vivo active-ATG levels after HCT.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell immune reconstitution (IR) after HCT is pivotal for disease control and reduces the probability of transplantation-related mortality. [1][2][3][4][5][6][7] To prevent rejection of the graft and graft-versushost disease (GVHD), antithymocyte globulin (ATG; Thymoglobulin, Genzyme) was introduced to conditioning regimens. ATG has a half-life of up to ;30 days 8 and is often still present during the first weeks after HCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation